Comparison of Wall Construction Costs Using Brick, Batako, and Hebel Materials in Denpasar City - Astariani, Ni Kadek; Partama, I Gusti Ngurah Eka; Putra, I Gusti Ngurah Gede Dirgayusa; Eratodi, I Gusti Lanang Bagus (ASTONJADRO, 2026)
A construction project is a series within a certain scope where work in the field certainly has a limited time. Several previous researchers conducted research on the comparative cost of wall materials and found that the cost of installing walls using bricks was cheaper than red bricks or bricks. Based on the results of previous research with a comparison of the costs of the three wall materials, namely brick, brick and Hebel as wall materials, in this research we will compare the work costs of the three materials Brick, Brick and Hebel with a case study in the SMA Negeri 9 Building Construction Project Denpasar. From the calculation of wall construction costs in the Denpasar 9 Public High School building construction project, the results obtained were that for walls made of brick material it was IDR. 425,894,615.49, walls made of brick material amounting to IDR 401,891,935.33 and for walls made of hebel material IDR. 507,619,946.90. From the results of the comparison of the total wall construction costs in the Denpasar 9 State High School Building Project, the cost of wall work using brick material is 5.80% higher compared to wall work using brick material, the cost of wall work using brick material is 17.65% lower than wall work using brick material. hebel material and the cost of wall work using brick material is 24.47% lower compared to wall work using hebel material. Brick material has the lowest work costs, brick material has higher work costs than brick but lower than hebel, while hebel material has the highest work costs.